Clinical evaluation of autologous platelet-rich plasma therapy for intrauterine adhesions: a systematic review and meta-analysis - Tang, Ruonan; Xiao, Xifeng; He, Yunan; Qiu, Daner; Zhang, Wanlin; Wang, Xiaohong (Frontiers in Endocrinology, 2023)
Objective: This meta-analysis aims to evaluate the efficacy and safety of autologous platelet-rich plasma (PRP) administration in reducing adhesion recurrence and improving pregnancy outcomes in patients with intrauterine adhesion (IUA). Methods: We conducted a comprehensive search of Pubmed, Embase, the Cochrane Library, Web of Science, Scopus, and China National Knowledge Internet (CNKI) from inception to February 10, 2023, without any language or regional restrictions. We used random-effects models to assess odds ratios (OR) and weight mean differences (WMD) with 95% confidence intervals. Results: Our meta-analysis included a total of 730 patients from 10 clinical studies (6 RCTs and 4 non-RCTs). The results showed that PRP administration significantly increased endometrial thickness (WMD = 0.79, 95% CI: 0.40–1.19; P < 0.001; I2 = 0.0%), menstrual volume (WMD = 2.96, 95% CI = 2.30–3.61; P < 0.001; I2 = 0.0%), and days of menstruation (WMD = 1.13, 95% CI = 0.86–1.41; P < 0.001; I2 = 0.0%). Additionally, the pregnancy rate was also improved (OR = 1.82, 95% CI: 1.19-2.78; P = 0.006; I2 = 0.0%). However, there was insufficient evidence to reach a conclusion regarding the effects of PRP on the recurrence rate of moderate to severe IUA, changes in AFS scores, miscarriage rate, and live birth rate. Conclusions: Our analysis confirms that autologous PRP is an effective treatment for IUA. However, the limited sample size suggests that the results should be interpreted with caution. Therefore, larger and well-designed studies are necessary in the future to confirm these findings and explore the optimal PRP dosing regimens further.